Revitalizing Oluhuta Paradise Through Community Based Tourism: Local Economy and Sustainable Tourism - Henro Nento; Apdul Gandi Igirisa; Kurniadi K. Hasan; Mohamad Fadly Binolombangan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to identify appropriate revitalization strategies for the management of the Oluhuta Paradise tourist attraction through a Community Based Tourism (CBT) approach to improve the local economy and achieve sustainable tourism. Oluhuta Paradise, located in Bone Bolango Regency, Gorontalo Province, has untapped tourism potential, with the main challenges being minimal infrastructure and low community participation in its management. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, field observations, and documentation studies. The results show that the application of the CBT model, which places local communities as the main actors in the planning, management, and utilization of tourism resources, can encourage community empowerment and create a more equitable distribution of benefits. In addition, the integration of sustainable tourism principles in the CBT model can ensure environmental sustainability and environmentally friendly natural resource management. This study also highlights the importance of community involvement in every stage of revitalization, from planning to implementation, to achieve long-term social, cultural, and economic sustainability.